The role of interleukin-17 in spondyloarthropathies and systemic lupus erythematosus: Two clinical cases in real - Paula Antunes; Rita Costa; Ana Gorgulho; António Marinho (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2022)
Spondyloarthropathies are known to affect the interleukin (IL)-17 activation pathway as a basis of their pathology, as is apparent from the literature. Recent studies established the vital role of IL-17 in the treatment of Systemic Lupus Erythematosus (SLE). This article aims to demonstrate the efficacy and safety of IL-17 in the treatment of both spondyloarthropathies and SLE by presenting two cases. The first case concerns a 30-year-old woman who was initially diagnosed with SLE. In the course of the disease, she developed spondyloarthritis and genital psoriasis. She was initially medicated with secukinumab but maintained severe genital psoriasis, the reason it was changed to ixekizumab with great improvement. The second case refers to a 40-year-old woman who previously had spondyloarthropathy with D12 enthesitis and sacroiliitis. Initial treatment with adalimumab led to a lupus-like syndrome, with persistent high systemic inflammatory response syndrome and extreme fatigue. Because of the recrudescence of axial complaints, secukinumab was started and the patient evolved with a global clinical response. Thus, the authors present two cases of spondyloarthropathy and SLE that document the efficacy and safety of IL- 17 blockers, which can lead to the incorporation of these agents in the treatment of SLE.